Fracture Mechanics: Nineteenth Symposium 1988
DOI: 10.1520/stp33072s
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the Amplitude of Stress Singular Terms for Cracks and Reentrant Corners

Abstract: The theoretical basis and performance characteristics of two new methods for the computation of the coefficients of the terms of asymptotic expansions at reentrant corners from finite-element solutions are presented. The methods, called the contour integral method (CIM) and the cutoff function method (CFM), are very efficient: the coefficients converge to their true values as fast as the strain energy, or faster. In order to make the presentation as simple as possible, we assume that the elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
4

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 19 publications
3
65
0
4
Order By: Relevance
“…One of the most efficient ways for extracting the GSIFs in a superconvergent manner is by indirect extraction procedure using the CIM and the CFM presented in [7,91. These efficient procedures use specially constructed extraction functions.…”
Section: Flux Intensity Factorsmentioning
confidence: 99%
“…One of the most efficient ways for extracting the GSIFs in a superconvergent manner is by indirect extraction procedure using the CIM and the CFM presented in [7,91. These efficient procedures use specially constructed extraction functions.…”
Section: Flux Intensity Factorsmentioning
confidence: 99%
“…One of the most efficient methods to extract the GSIFs for cracked configurations is the contour integral method (CIM) first introduced in [7], and incorporated for 2-D elasticity in [8]. For detailed discussion on the CIM we refer to [7][8][9], where it has been shown that the method yield superconvergent results.…”
Section: U = ~ ~Cirnr Ai Lnm(r)fim(o)+u*(ro)mentioning
confidence: 99%
“…2 For the way to compute stress intensity factors we refer to [17], and [18]. It has been shown that the optimal number n of layers of elements increases with the polynomial degree p, that the optimal ratio of the geometric mesh is independent of the strength of the singularity, p, and the number n of layers and has a magnitude of .15.…”
Section: The Elasticity Problem On a Polygonal Domain And Its Basic Pmentioning
confidence: 99%
“…In two numerical examples we will show the steps of the expert system as shows mode 1 stress distribution given, for example, in [18]. The solution * has singular behaviour at the reentrant corner.…”
Section: Numerical Examplesmentioning
confidence: 99%